Time varying backstepping control for trajectory tracking of mobile robot - Obaid, M. A. M. (Inderscience Publishers, 2017)
This paper presents a time varying backstepping tracking controller (TVBTC) for the kinematic model of the non-holonomic wheeled mobile robot (WMR) that can improves the transient performances of the standard backstepping control scheme. The proposed TVBTC is derived based on the analysis of the error dynamic, as well as the stability conditions of the controlled system. The asymptotic stability of the system and the convergence of the posture errors to zero are guaranteed using the Lyapunov stability theory. In comparison with the other tracking control methods for the mobile robot, the simulation results demonstrate that the transient performance can be improved significantly using the proposed TVBTC, which is capable to track a circular path with faster settling time and minimal overshoot. In addition, the TVBTC can efficiently handle a situation with arbitrarily large initial tracking errors and it is capable to produce smooth and bounded velocity output in a finite time interval. The simulation results show the effectiveness of the proposed tracking controller at the starting time.